The Effectiveness of Different Content Transfers on the Example of Elementary School Students - Ampulska, Patrycja (Przegląd Badań Edukacyjnych (Educational Studies Review), 2016)
The paper presents the results of experimental research conducted in primary schools. The aim of the research was to check the effectiveness of different content messages. Experimental inquiry was based on dual coding theory of Allan Paivio which states that the use and transmission of image and voice stimuli are coded in two. Using both ways of transfer leads to additivity effects of memory and, at the same time, increases the level of memorized content. Trying to answer thequestion whether the level of memorized content among students is dependent on the type of transmission, it was hypothesized that the respondents in the audiovisual group will show the highest level of memorized material.